Assessment of Prevention of Periodontal Diseases in Pregnant Women in Tbilisi (in English and Georgian) - Tevzadze, Veriko; Nanobashvili, Ketevan (Caucasus Journal of Health Sciences and Public Health, 2020)
Despite significant successes in the field of oral health, dental diseases still remain a topical and acute problem especially among the underprivileged groups of the world population, both in developed and developing countries. Periodontal inflammatory diseases are the most widespread among dental diseases, in the development of which the main etiological role is given to a microbe, although these diseases are multifactorial and many local and general factors affect their origin and development. Pain, discomfort, and tooth loss, developed due to periodontal disease, cause functional and aesthetic disorders and hinder a person’s healthy integration into society. Dental diseases require a serious professional approach and treatment in order to prevent further complications of the disease. Equally important is the relationship between the oral cavity of a pregnant woman and the health of the fetus. Gingivitis in pregnant women is the most common problem during the gestation period - according to some studies, it is found in 30% of pregnant women, while others name 100% as well. It is also known that 50% of infants (3 months of age) have periopathogenic microflora, the very source of which is infected mothers. The availability of dental care worldwide is significantly lower in the elderly, as well as in people with low education and income, hence the health of the oral cavity is impaired in the population of low social status. Therefore, the creation of such public projects and programs that provide maximum involvement of the poor and low social strata in the treatment and prevention of oral diseases is the prerogative of healthcare and the state. Traditional medical dental service is a significant economic burden in the developed countries of the world, where 5-10% of the public health budget is spent on treatment and prevention of oral diseases; public oral health programs are rare in the low and middle-income developing countries. High costs of dental services can be avoided with effective prevention, and well-planned prevention is an important step in reducing diseases. Despite the optimistic trends in the incidence and severity of oral diseases in recent years, periodontal diseases are very common in most countries of the world and cover the vast majority of adult population.